Hydrothermal synthesis of lead titanate fine powders at water boiling temperature - Chankaew C. (2014)
Lead titanate fine powders comprising of a single tetragonal phase and well characterized particles were successfully synthesized at an exceptionally low temperature of 100°C. The important role of the ultrasonication in reducing the thermodynamic barrier of the hydrothermal reaction, and the slow rate of hydrothermal reaction at 100°C were underlined. The synthesized particles were revealed to be tetragonal in shape, mostly submicrometers in size, and generally present as large aggregates. The layer-by-layer model was also proposed as the particle growth mechanism.